Adequacy of nutritional support in critically ill patients post implementation of nutritional protocols in surgical intensive care unit of a university hospital - Ikram, Sarah; Abdur Rehman Aleemi; Hashmi , Madiha; Zareen Imam (Journal of the Pakistan Medical Association, 2022)
Objective: To evaluate improvement in nutrition support therapy after the implementation of nutritional protocols in critically ill surgical patients. Methods: The ambidirectional study was conducted at the surgical intensive care unit of Aga Khan University Hospital, Karachi, using an evidenced-based nutritional protocol. The pre-protocol retrospective data group A comprised patient records from July to September 2018, while the post-protocol prospective data group B related to the period between October and December 2018. Both data sets involved patients of either gender aged at least 18 years who needed admission to surgical intensive care unit and were unable to take oral nutrition for >2 days and remained under intensive care for up to seven days. Data was analysed using SPSS 21. Results: Of the 65 patients, 30(46.2%) were in group A; 21(70%) males and 9(30%) females with mean age 40±16.55 years (range: 18-80 years). The remaining 35(53.8%) were in group B; 27(77%) males and 8(23%) females with mean age 48.66±17.7 years (range: 18-86 years). Nutritional screening indicated that 16(53.3%) patients in group A and 35(100%) in group B were at the risk of developing malnutrition. Patients receiving enteral nutrition within 24 hours of admission increased from 7(23.35%) in group A to 17 (48.3%) in group B. Overall, the amount of enterally administered calories increased from mean 321057±2495 kcal (29.6%) in group A to mean 384585±2343 (92.6%) in group B. ---Continue